VD_FINDINFO HC / 2011 / 82 vom 15. Februar 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE | 257d CO, 457 CPC, 23 LPEBL, 24 LPEBL, 29 LPEBL